2019
DOI: 10.1016/j.brainres.2018.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Changes in striatal dopamine release and locomotor activity following acute withdrawal from chronic nicotine are mediated by CRF1, but not CRF2, receptors

Abstract: Male Wistar were exposed to repeated ip injection with nicotine for 7 days.• On the 8th and the 9th day rats were injected icv with antalarmin or astressin 2B .• Horizontal and vertical locomotor activities changed on the 8th and the 9th day.• Dorsal and ventral striatal dopamine releases changed on the 8th and the 9th day.• All the changes observed were attenuated by antalarmin, but not astressin 2B .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
3
3
0
Order By: Relevance
“…In the current work, we observed that during early (day 4) nicotine withdrawal, rats displayed increased horizontal locomotor activity in a nonfamiliar environment, which is in agreement with previous study [39]; however, there are other reports showing no change or decrease in locomotion [36,40]. Interestingly, we show that the augmented motor reactivity to novelty in drug-weaned animals was attenuated by both doses (0.1 and 0.3 mg/kg) of lorcaserin administered for 4 days.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current work, we observed that during early (day 4) nicotine withdrawal, rats displayed increased horizontal locomotor activity in a nonfamiliar environment, which is in agreement with previous study [39]; however, there are other reports showing no change or decrease in locomotion [36,40]. Interestingly, we show that the augmented motor reactivity to novelty in drug-weaned animals was attenuated by both doses (0.1 and 0.3 mg/kg) of lorcaserin administered for 4 days.…”
Section: Discussionsupporting
confidence: 93%
“…Considering the potential underlying mechanism of action of lorcaserin, different brain regions must be taken into account. Concerning the locomotor hyperactivity which is thought to reflect enhanced DA neurotransmission in the nucleus accumbens [60], indeed, there are supporting data that show that the increase in animals' motor behavior during early nicotine cessation may be related to dysregulation in the striatal DA system [39]. Recently, it has been shown that acute treatment with lorcaserin attenuated the activity of DA neurons in the ventral tegmental area (brain region rich in 5-HT 2C receptors localized on tegmental GABA interneurons, their terminals, and on DA cells [61,62]), but did not affect DA release in the striatum [63].…”
Section: Discussionmentioning
confidence: 86%
“…These findings integrate and expand previously published data indicating that Crf/CrfR1 sustain and maintain an anxiogenic and stressful state after nicotine WDW [68,69]. In the case of acute experiments, this stressful response is probably due to the activation of CrfR1 [70,71], and can be counteracted by the administration of CrfR1 antagonists [72].…”
Section: Discussionsupporting
confidence: 89%
“…In parallel, the dorsal and ventral striatal dopamine release increased significantly in nicotine-treated group, compared with the saline-treated group (Figure 14). All the changes observed on the 8 th day were reduced significantly after treatment with antalarmin, but not astressin 2B [69] ( Figures 13-14).…”
Section: After 12 Hours Of Nicotine Withdrawalmentioning
confidence: 94%
“…The other half of the animals were treated ICV on the 9 th day (after 24 hours following the last IP administration) based on the same treatment protocol. Hence, rats were divided in 6 groups: group 1. saline IP + saline ICV; group 2. saline IP + antalarmin ICV; group 3. saline IP + astressin 2B ICV; group 4. nicotine IP + saline ICV; group 5. nicotine IP + antalarmin ICV; and group 6. nicotine IP + astressin 2B ICV [69]. The doses of nicotine and the schedule of administration chosen were expected to produce plasma nicotine levels in rats similar to plasma nicotine levels found in an individual who smokes 1-2 packs of cigarettes per day [76].…”
Section: Treatmentmentioning
confidence: 99%